Analysis of Outpatient Type 2 Diabetes Mellitus Treatment Patterns: A Four-Criteria Framework at Sanjiwani Hospital, Gianyar - Widowati, I Gusti Ayu Rai; Kusuma, Kadek Ari Teja; Dewi, Dewa Ayu Putu Satrya (Bali Medical and Wellness Journal, 2024)
Background: Diabetes mellitus is a chronic condition with high blood sugar levels caused by insufficient insulin production. Improper prescribing can lead to ineffective treatment, increased health risks, and resource wastage. Objective: This study aims to assess compliance with four essential criteria for rational drug use in treating Type 2 Diabetes Mellitus (DM2) patients at Sanjiwani Hospital in Gianyar. By examining these areas, the study seeks to identify opportunities for improving DM2 treatment and ensuring that practices align with established standards to enhance patient outcomes and safety. Methods: A cross-sectional survey was conducted from May to June 2024, analyzing purposively collected prescriptions. A total of 113 prescriptions were reviewed to assess prescribing practices. Results: The study evaluated prescribing accuracy based on four criteria: drug selection, dosage, indication, and timing. Results showed 100% accuracy in drug selection and indication, 76.1% accuracy in dosage, and 78.8% accuracy in timing. Conclusion: These findings suggest that medication practices at Sanjiwani Hospital for DM2 patients are generally satisfactory. However, pharmacists should play an active role in providing pharmaceutical information and counseling to achieve the best clinical outcomes. This includes ensuring correct dosage and timing to improve overall treatment effectiveness and patient safety.